Land drainage and flood defence responsibilities a practical guide. - Howarth, William; McGillivray, Donald, 1967- (Thomas Telford, 1996)
Useful for both civil engineers and professionals who are concerned with the practice of land drainage. This edition incorporates the following major developments: The Environment Act 1995; The Land Drainage Act 1994; The Conservation Regulations 1994; The Coal Industry Act 1994; and The Local Government Act 1992 and the Local Government Act 1994.